2020
DOI: 10.1186/s12935-020-01261-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 promotes triple-negative breast cancer cells invasion and metastasis through the p53/TNFAIP8 pathway

Abstract: Background: Long non-coding RNA H19 (lncRNA H19) has been implicated in tumorigenesis and metastasis of breast cancer through regulating epithelial to mesenchymal transition (EMT); however, the underlying mechanisms remain elusive. Methods: LncRNA H19 and TNFAIP8 were identified by qRT-PCR and western blotting. CCK-8 assay, clone formation assay, transwell assay, and flow cytometry assay were performed to determine cell proliferation, migration, invasion and cell cycle of breast cancer respectively. Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…LncRNA, as a highly active RNA, has been proved to participate in the genesis and development of a number of tumors [4]. Among them, lncRNA H19 has been found to be abnormally expressed in human malignant tumors and regulates cell proliferation, migration, invasion, antiapoptosis, and epithelial-mesenchymal transition (EMT) through various mechanisms, thus playing a carcinogenic or anticancer role [5][6][7]. H19 has been found to act as a microRNA sponge to indirectly regulate the expression of microRNA downstream target genes thus mediating cancer progression in several cancer types [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA, as a highly active RNA, has been proved to participate in the genesis and development of a number of tumors [4]. Among them, lncRNA H19 has been found to be abnormally expressed in human malignant tumors and regulates cell proliferation, migration, invasion, antiapoptosis, and epithelial-mesenchymal transition (EMT) through various mechanisms, thus playing a carcinogenic or anticancer role [5][6][7]. H19 has been found to act as a microRNA sponge to indirectly regulate the expression of microRNA downstream target genes thus mediating cancer progression in several cancer types [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact effects of dysregulated lncRNA expressions have yet to be fully determined. Both breast cancer cell lines and samples, especially those of TNBC, have been found to harbor high expressions of lncRNA H19, which has been implicated to increased rates of metastasis and tumorigenesis (10). Moreover, lncRNA H19 may promote breast cancer tamoxifen resistance through modulation of the SAHH/DNMT3B axis (11).…”
Section: Introductionmentioning
confidence: 99%
“…H19, as a ceRNA, acted as a miR-140-5p sponge, resulting in regulated the expression of FGF9. Li et al found that H19 stimulates osteogenic differentiation of rat BMSCs via the H19/miR-149/SDF-1 axis (Li et al 2020a , b ). Overexpressed H19 and SDF-1 and poorly expressed miR-149 were found in rats with osteogenic differentiation.…”
Section: The Role and Mechanism Of H19 In Osteogenic Differentiationmentioning
confidence: 99%
“…In recent years, mounting evidence has shown that various new bioinformatical and experimental strategies have identified a large number of novel lncRNAs (Lee and Bartolomei 2013 ; Batista and Chang, 2013 ; Alipoor et al 2020 ). LncRNAs could regulate gene expressions through interactions with DNAs, RNAs, protein (Koch 2017 ; Ali and Grote 2020; Cardon et al 2020 ; Li et al 2020a , b ; Zhang et al 2021 ), including chromatin remodeling, as well as transcriptional, post-transcriptional and epigenetic regulations (Lee and Bartolomei, 2013 ; Fatica and Bozzoni, 2014 ; Graf and Kretz 2020 ; Li et al 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation